Flood-Irrigated Grain Sorghum Cost-Return Budget - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1997)
This publication projects a budget that reflects expected income and costs based on flood-irrigated grain sorghum production.
MF580_1997_10
Keywords: MF580; Economics; Crops; MF